Redefining the Tea Green Leafhopper: Empoasca onukii Matsuda (Hemiptera: Cicadellidae) as a Vital Asset in Premium Tea Production - Unisa Conteh Kanu; Zhaohong Wang; Chenshi Qiu; Qiaojun Wen; Xueyan Li; Dongliang Qiu; Yinwei Gan; Runqian Mao (Life)
This review explores the evolving role of the tea green leafhopper, Empoasca onukii, in the tea industry, transitioning from a recognized pest to a significant enhancer of tea quality. Recent research highlights how its feeding behavior stimulates the production of desirable secondary metabolites, thereby improving the flavor profiles and market value of premium teas, particularly varieties like Taiwan’s “Oriental Beauty”. As consumer demand for unique and artisanal teas rises, the economic benefits associated with E. onukii are becoming increasingly evident, prompting farmers to adopt sustainable agricultural practices that often involve reduced pesticide use. Furthermore, the dynamic interplay between climatic factors, E. onukii population dynamics, and tea cultivation practices necessitates integrated pest management strategies that balance the beneficial and detrimental impacts of this leafhopper. Understanding these complexities not only fosters sustainable production methods but also opens niche markets, benefiting local economies and promoting both economic viability and environmental sustainability in the tea industry.